Carotenoids in bacteria : general scheme on the diversity of the biosynthetic pathways (2020)
Carotenoids are common and diverse molecules found in several organisms including Bacteria. They are terpenoids-based molecules produced in all phototrophic bacteria as well as in some non- phototrophic ones. In this short review, the literature of carotenoids in Bacteria was collected and studied to understand basic concepts from the definition of a carotenoid to the steps involved in synthesis, dividing them into isoprenoid precursors synthesis or carotenogenesis processes. Carotenoid diversity is also explored, as well as the classification, depending on the number of carbons or a biosynthetic pathway belonging to a specific bacterial group. Finally, the well described carotenoid biosynthesis routes found in four carotenoid-producing bacterial groups are explained: Cyanobacteria, Purple Bacteria, Green Sulfur Bacteria, and Non-Phototrophic Bacteria. This review is important for those scientists studying the applications of carotenoids in diverse industries